Gold Nanorods-Based Theranostics for Simultaneous Fluorescence/Two-Photon Luminescence Imaging and Synergistic Phototherapies. (7th February 2016) - Fang, Shan; Li, Chunxiao; Lin, Jing; Zhu, Haigang; Cui, Daxiang; Xu, Yunsheng; Li, Zhiming
Abstract : Gold nanorods (GNRs) have shown great potential applications in cancer theranostics due to the unique phenomenon of surface plasmon resonance, which leads to strong electric fields on the surface and consequently enhances the absorption and scattering in the near-infrared (NIR) region. Indocyanine green (ICG), an amphipathic dye, is not only an excellent NIR imaging agent but also an ideal light absorber for laser-mediated photodynamic and photothermal therapy. In this study, in order to integrate the merits of GNRs and ICG in biomedical applications, we developed ICG conjugated silica-coated GNRs (GNR@SiO2 -ICG) for cancer imaging and phototherapy. The covalent coupling strategy reduces the probability of leakage/desorption during the delivery. The as-prepared GNR@SiO2 -ICG could serve as efficient probes to simultaneously enhance fluorescence (FL) imaging and two-photon luminescence (TPL) imaging. In vitro experiments indicated that A375 cells could be killed through synergistic phototherapies effect of GNRs and ICG using single wavelength continuous-wave laser irradiation. Our results indicated that the synthesized GNR@SiO2 -ICG are effective for simultaneously enhancing FL/TPL imaging and synergistic phototherapies.